Workplace Challenges and Violence against Nurses: Subject Review - Waleed Ibrahim Saad, Abid Salih Kumait, Nasir Muwfaq Younis (Pakistan Journal of Medical & Health Sciences, 2023)
The "World Health Organization (WHO) defines workplace violence as, Incidents where staff are abused, threatened, or assaulted in circumstances related to their work, including commuting to and from work, involving an explicit or implicit challenge to their safety, well-being, or health." (WV) is listed as one of the world’s leading causes of workplace disability, and is widespread in health settings in Arab countries and Iraq as well. Nursing staff have the highest recorded incidence of interpersonal violence in Iraq, posing a major concern for healthcare professionals. Different researchers concentrate on prevalence rates of violence against nurses in hospitals, addressing forms of violence, position and background of violence in the workplace. Thus, some form of occupational violence has been encountered by most Iraqi nurses,that may contribute to harm and abuse and reduced job performance. Reports have described the impact of violence in the workplace on the employee satisfaction of nurses and patient safety, but few studies have been done about whether aggression in the workplace influences patient safety via employee satisfaction. Ultimately, abuse against nurses is perceived by the nursing community to be a dynamic and chronic workplace risk. In the health care sector, nurses are among the most abused staff. Nurses are too often subject to abuse, primarily from clients, relatives of patients, visitors and caregivers team. The purpose of this article is to review the violence against nurses and challenges work place.